Assessing health-related quality-of-life in patients with symptomatic obstructive hypertrophic cardiomyopathy: EQ-5D-based utilities in the EXPLORER-HCM trial. (31st December 2022) - Xie, Jipan; Wang, Yan; Xu, Yaping; Fine, Jennifer T.; Lam, Jenny; Garrison, Louis P.
Abstract: Aims: To assess the effects of mavacamten on health-related quality-of-life (HRQoL) in symptomatic obstructive hypertrophic cardiomyopathy (HCM) and estimate health utilities by New York Heart Association (NYHA) functional class. Materials and methods: Patients with symptomatic obstructive HCM were randomized to 30 weeks of mavacamten or to placebo treatment, with or without beta-blocker or calcium channel blocker monotherapy, in EXPLORER-HCM (ClinicalTrials.gov identifier: NCT03470545). Health utility was measured using the EuroQoL 5-dimension 5-level (EQ-5D-5L) index score with the US value set. The 30-week changes in EQ-5D-5L index score and EuroQoL visual analog scale (EQ-VAS) score were compared between the two arms using linear regression, and the proportions of patients with a meaningful improvement were compared using logistic regression. The meaningful change thresholds were estimated using both distribution- and anchor-based approaches. Mean utilities by NYHA class were estimated for each arm using a generalized estimating equation. Results: Compared with placebo ( N  = 89), patients receiving mavacamten ( N  = 96) had significantly greater 30-week improvement in EQ-5D-5L index score (mavacamten = 0.084; placebo = 0.009; adjusted difference = 0.073 [95% confidence interval = 0.027–0.118]) and EQ-VAS score (mavacamten = 8.5; placebo = 0.7; adjusted difference = 7.5 [95% confidence interval = 1.8–13.2]), and a significantly higher proportion of these patients showed meaningful improvement in EQ-5D-5L index score and EQ-VAS score. Both outcomes were correlated with the Kansas City Cardiomyopathy Questionnaire Clinical Summary Score (KCCQ CSS) and HCM Symptom Questionnaire Shortness-of-Breath (HCMSQ SoB) subscore, two patient-reported anchor variables. Additionally, mean utilities significantly decreased with higher NYHA functional class (values for NYHA class I, II, and III/IV – mavacamten = 0.950, 0.866, and 0.708; placebo = 0.952, 0.850, and 0.704). Conclusions: Compared with placebo, mavacamten significantly improved EQ-5D-5L index score and EQ-VAS score – and thus HRQoL – among patients with symptomatic obstructive HCM. Patients with a higher NYHA functional class had a lower health utility value.